2019
DOI: 10.2478/hukin-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Training Load, Muscle Soreness, Stress, Fatigue, and Sleep Quality in Professional Basketball: A Full Season Study

Abstract: This study aimed to compare the perceived training load (session-RPE) and wellness status (muscle soreness, stress, fatigue, and sleep quality) within and between regular (one-match) and congested (two matches) weeks. Fifteen professional basketball players from a European First league club participated in this study. Wellness status (Hooper’s questionnaire) and perceived training loads (session-RPE) were measured for each training session and matches over a full season. Regular weeks presented moderately grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 38 publications
4
48
0
1
Order By: Relevance
“…In relation to the comparison of the internal load in weeks with different competitive densities, the results obtained in the present study for the season 2018-2019 were similar to those reported by Manzi et al [4] and Clemente et al [7], where no differences were found in the effort perceived by players in weeks with one or two games. The lack of consensus on the differences regarding the cumulative load in weeks with different competitive densities may be due to the fact that the data shown by Conte et al [7] and Manzi et al [4] were not collected throughout a whole season, but only for a specific period of time within a season. Teams use different load strategies during a season depending on the importance of the moment [4], and this would explain the different results obtained among the studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In relation to the comparison of the internal load in weeks with different competitive densities, the results obtained in the present study for the season 2018-2019 were similar to those reported by Manzi et al [4] and Clemente et al [7], where no differences were found in the effort perceived by players in weeks with one or two games. The lack of consensus on the differences regarding the cumulative load in weeks with different competitive densities may be due to the fact that the data shown by Conte et al [7] and Manzi et al [4] were not collected throughout a whole season, but only for a specific period of time within a season. Teams use different load strategies during a season depending on the importance of the moment [4], and this would explain the different results obtained among the studies.…”
Section: Discussionsupporting
confidence: 91%
“…The weekly accumulated internal load values observed for the team in the present study (~3150 AU) were higher than the 2520 AU of the Lithuanian female players [5], similar to the 3200 AU of professional players [7] and lower than the Brazilian female team, where values above 4000 AU were reported [12]. A comparison with collage and Italian professional players showed that the sRPE values were lower than the results shown in this study for W1 and W2 in both seasons [4,6].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The results of the present study suggest that a prophylactic approach, such as ankle taping, is effective for the ROM restriction of the ankle joint immediately after the taping application in soccer and basketball players without differences between groups. However, in the final minutes of the session, where the intensity and the fatigue levels were at its highest peak [23], the ROM values were similar to the baseline values.…”
Section: Discussionmentioning
confidence: 57%